Effects of running shoe construction on performance in long distance running - Nigg, B. M.; Cigoja, S.; Nigg, S. R. (Footwear Science, 2020)
It has been claimed that wearing the Nike Vaporfly 4% (and its iterations) can result in increased running economy of (on average) about 4%. However, researchers still lack clear evidence as to which footwear features caused these performance improvements and how much the corresponding improvement are. Based on the discussions of this letter to the editor, it seems to be inadequate to speculate that therecent world records in 100 km, marathon, half-marathon, and 15 km were primarily broken due to increased midsole thickness. As a matter of fact, we suggest that the effect of the midsole is less than 1%. We propose that an appropriated use of a bent midsole stiffening is the main contributor and that these contributions to improvement in running performance can easily be 6%. Therefore, it appears inappropriate to regulate one specific footwear feature (i.e. midsole characteristics) before understanding where these performance advantages originated from. However, ourcurrent knowledge suggests that, compared to the teeter-totter effect, all other shoe characteristic contributions to running performance are relativelysmall or negligible. Based on our understanding, we have summarised the different potential performance improvements due to specific shoe features. Based on the results in the table, it seems obvious that the curved stiff sole, the corresponding teeter-totter effect and the additional force on the heel during take-off are the major contributors to the improved performance.